A Comparative Analysis of Choorna and Bhavitha Choorna of Flower Buds of Japa (Hibiscus rosa-sinensis Linn.) through High-performance Thin-layer Chromatography - Smrithi, S; Shincymol, V V; Ansary, P Y; Oommen, Sara Moncy (International Research Journal of Ayurveda & Yoga, 2023)
Introduction:High-performance thin-layer chromatography (HPTLC) is nowadays adopted by the major pharmacopoeias of the world for analysis of herbal drugs and preparations. The current use is generally limited to the visual observation of the fingerprints for identification and detection of adulterations and falsifications. It makes sense to use HPTLC to expand chromatographic fingerprints to identify the main active ingredients in medicinal plants. Compared to thin layer chromatography, the separation and resolution are significantly superior, and the outcomes are far more consistent and repeatable. Materials and Methods: Japakusuma mukula (flower buds of Japa) which is botanically identified as Hibiscus rosa sinensis Linn. contains various phytoconstituents such as flavonoids, terpenoids, steroids, polysaccharides, alkaloids, amino acids, lipids, sesquiterpene, quinones, and naphthalene groups. HPTLC fingerprinting profile of choorna (powder) and bhavitha choorna (triturated powder) of flower buds of Hibiscus rosa-sinensis Linn. is demonstrated in methanolic extract in this study and bands are analyzed at 254 nm and 366 nm using CAMAG Linomat V Automatic Sample Spotter. The peaks and area are compared. Results and Conclusion: Similarity in the peak areas even in different Max Rf values, it could be inferred that the phytoconstituent obtained in both conditions will be having similarity. Since the bhavitha choorna possess, the greater number of large value peak areas in both the wavelength of visualization, it is clear that bhavitha choorna is more potent in comparison with choorna.